Analysis of Risk of Sever Hypocalcaemia after Thyroidectomy Among Local Population of Pakistan (Medical Forum Monthly, 2020)
Objective: To analyse the risk of sever hypocalcaemia after thyroidectomy among local population of Pakistan.Study Design: Correlational studyPlace and Duration of Study: This study was conducted at the Department of General Surgery, DHQ Teaching Hospital Gujranwala during May 2019 till October 2019,Materials and Methods: This study was done with the permission of ethical committee of hospital. The data was collected from 100 patients. The serum calcium and parathyroid hormone (PTH) level of patients were tested.Results: The data was collected from 200 patients of both genders. All patients had normal (9.5-75 pg/ml) pre-operative PTH and normal calcium levels (8.0-10.4 mg/ dl). A total of 50 patients developed hypocalcaemia after surgery.Conclusion: It is concluded that postoperative hypocalcaemia rate were fundamentally related to the degree of thyroidectomy, sex, sidelong lymph hub analyzation, employable time, and utilization of CNs.